2021
DOI: 10.1002/jor.25023
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibition preferentially suppresses anchorage‐independent growth in osteosarcoma cells and decreases tumors in vivo

Abstract: Osteosarcoma is the most common high‐grade malignancy of bone, and novel therapeutic options are urgently required. Previously, we developed mouse osteosarcoma AXT cells that can proliferate both under adherent and nonadherent conditions. Based on metabolite levels, nonadherent conditions were more similar to the in vivo environment than adherent conditions. A drug screen identified MEK inhibitors, including trametinib, that preferentially decreased the viability of nonadherent AXT cells. Trametinib inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has also been reported that MEK inhibition can inhibit osteosarcoma cell growth and thus reduce tumor growth in vivo. According to the study, the growth of osteosarcoma cells was diminished when MEK was inhibited, thus reducing tumor growth in the body [20]. These studies all suggest that the MAPK pathway exerts a weighty influence on the process of osteosarcoma development.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been reported that MEK inhibition can inhibit osteosarcoma cell growth and thus reduce tumor growth in vivo. According to the study, the growth of osteosarcoma cells was diminished when MEK was inhibited, thus reducing tumor growth in the body [20]. These studies all suggest that the MAPK pathway exerts a weighty influence on the process of osteosarcoma development.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, tumors derived from AX cells or the p53-knockout cells exhibited the same histological findings, including osteoid and bone formation (data not shown). Given that AX cells express GFP, GFP expression using total RNA extracted from blood or tissues can be used to quantify circulating tumor cells or metastatic lesions, respectively [ 41 ]. Although there were quantitative variations, knockout of p53 did not significantly affect the amount of circulating tumor cells or lung metastasis ( Figure 3 e,f) These findings suggest that the simultaneous presence of the wild-type p53 allele and the R270C mutation did not alter tumor initiation or the progression of osteosarcoma in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…AXT cells are highly tumorigenic in syngeneic C57BL/6 mice [ 6 , 7 , 8 , 9 , 10 , 41 ]. We examined the role of mutant p53 in tumorigenesis and tumor progression and investigated whether mutant p53 could be a potential target for osteosarcoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shimizu et al reported that MEK inhibition with trametinib inhibited the cell cycle and induced apoptosis in non-adherent-growing U2OS cells. Moreover, trametinib decreased the size of primary tumors and circulating tumor cells in an in vivo mouse model [ 124 ].…”
Section: Mechanisms Of Csc Resistance To Conventional Therapiesmentioning
confidence: 99%